Structural Determinants of Intention to Leave in Healthcare and Social Medicine-Based Strategies to Counteract It (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The intention to leave represents a critical phenomenon in the health-care sector, with significant implications for the quality of care and health equity. Despite extensive existing literature, a systemic understanding that takes into account the social and structural determinants of the phenomenon is lacking. By reviewing the international literature (2019–2024), this paper aims to identify – from a social medicine perspective – the determinants and policies for addressing the intention to leave at the macro-structural, meso-organizational, and micro-individual levels.